Identification of heat tolerant genotypes of chili pepper based on cell membrane thermostability and expression of heat shock protein genes - Usman, Magaji G. (2014)
Terminal heat stress leads to change in the various parameters, such as heat shock protein genes and cell membrane thermostability, in chili pepper and is an important component of thermotolerance capacity. Experiments were carried out at Agrotechnology Unit, Agro Gene Bank and the Plant Physiology Laboratory, Institute of Tropical Agriculture, Universiti Putra Malaysia to study the mechanisms for heat tolerance in chili pepper genotypes. To assess these mechanisms, 36 genotypes were evaluated for morpho-physiological characters, cellular membrane thermostability (CMT) and for HSP70 gene expression. Significant (p <0.05) variation was observed among the genotypes for all the characters with genotypes AVPP9905 (1144.3 g) and Kulai (818.1 g) recording the highest yield per plant except chlorophyll content and days to flowering. The plants from selected chili pepper genotypes for CMT and HSP70 gene experiments were grown in experimental plant growth chamber for 4-8 weeks after sowing. The mean value of CMT indicates in most of the genotypes that membrane integrity was not damaged by the high temperature treatment (50ºC), with a mean value of 64.64%. The genotypes were classified based on heat tolerant (>60%), moderately tolerant (30%- 60%) and susceptible (<30%). Genotypes AVPP0702, AVPP0116 and AVPP9905 recorded the highest CMTs, at 89.27%, 89.27% and 85.10% respectively. AVPP9703 and AVPP0002 gave CMTs of 15.87% and 18.43%, respectively which might indicate their sensitivity to heat stress. HSP70 gene was identified and found differentially expressed under heat stress condition. Under heat stress, significantly increased levels of the HSP70 genes were detected after 2 hours temperature treatment at 42°C, which indicated these genes are quickly and sharply induced by heat shock. This was found especially true for all genotypes which were significantly up-regulated by more than 36.9, 7.10, 3.87 and 3 fold, for AVPP0702, AVPP0116, AVPP0002 and AVPP9703, respectively. Variety Kulai was found to be significantly down regulated under heat stress. Genotypes AVPP0702, AVPP9905 and AVPP0116 could be considered as heat tolerant genotypes while Kulai and AVPP9703 as heat sensitive genotypes from this study. The result further proves that CMT and HSP70 are key components of the defense mechanism against heat stress in chili pepper.